UiTM earns global recognition in the Times Higher Education World University Rankings by Subject 2025 - UiTM, UiTM Global (Office of International Affairs (OIA), 2025)
Universiti Teknologi MARA (UiTM) has earned recognition from the Times Higher Education (THE) World University Rankings by Subject 2025. marking another milestone in the university's global presence. The THE World University Rankings by Subject 2025 methodology is designed to evaluate universities across 11 subject areas using a refined version of 18 performance indicators. These indicators are categorized under five core pillars: Teaching, Rescarch Environment, Research Quality, Industry, and International Outlook. Comparcd to the QS World University Rankings by Subject, THE tends to focus more on research output, research reputation, research quality, and industry income, which are essential for assessing knowledge transfer. UiTM was ranked in 10 subjects overall, with an outstanding position of 301+ in Law, placing it among just four universities in Malaysia listed for this discipline. This notable achievement underscores UiTM's dedication to enhancing the quality of law education on the global stage. UiTM was also ranked 501-600 in Education Studies (formerly Education), 601+ in Arts and Humanities, 601-800 in Business and Economics. 801-1000 for Life Sciences and Social Sciences, 1001-1250 for Engineering. and 1001+ for Physical Sciences, Computer Science, and Medical and Health (formerly Clinical and Health) according to the 2025 THE World University Rankings by Subject, released today. This achievement reflects UiTM's continued growth and competition at the global level while making a positive impact across various academic fields.